Dynamic magnetic resonance imaging as an outcome predictor for lung-volume reduction surgery in patients with severe emphysema. (13th August 2018) - Martini, Katharina; Caviezel, Claudio; Schneiter, Didier; Milanese, Gianluca; Opitz, Isabelle; Weder, Walter; Frauenfelder, Thomas
Abstract: OBJECTIVES: We hypothesize a significant correlation between parameters of preoperative dynamic magnetic resonance imaging (MRI) and postoperative outcomes measured by pulmonary function tests. METHODS: Dynamic MRI of the lungs was prospectively performed during 2 breath cycles 1 day before and 3 months after surgery, herein termed as pre- and post-lung-volume reduction surgery (LVRS) MRI. Quantitative measurements were performed on sagittal planes for the left lung and right lung: lung height, anteroposterior diameter, hemidiaphragm height and area as well as perimeter. Additionally, dynamic changes in hemidiaphragmatic area and height were measured. Parameters were normalized by patients' height. Pulmonary function test pre-LVRS and post-LVRS was performed. The cut-off value for treatment benefit was defined as a 30% increase in forced expiratory volume in 1 s. RESULTS: Thirty-nine consecutive patients (15 women, median age 61 years) were included. On expiration, the mean lung area on both sides ( P right = 0.001 and P left = 0.016) and anteroposterior diameter of the right lung ( P right = 0.003) improved post-LVRS. Dynamic measurements showed differences pre- and post-LVRS on the right lung but not on the left lung ( P right < 0.001 and P left = 0.090). There were no significant changes in lung height for both sides, in hemidiaphragmatic height on the right as well as diaphragmatic area pre- and post-LVRS ( P > 0.05). Except for hemidiaphragmatic height on the left lung ( P = 0.039), no significant differences were found on inspiration. Considering the 30% cut-off for treatment benefit, the receiver operating curves analysis indicated a height-normalized expiratory lung area ≥35 793 mm 2 as the most sensitive preoperative outcome predictor (sensitivity = 86%; specificity = 61%). CONCLUSIONS: Preoperative dynamic MRI can be used as an additional outcome predictor for patient selection in LVRS. A height-normalized total lung area in expiration ≥35 793 mm 2 correlates with a 30% increase in forced expiratory volume in 1 s. Clinical trial registration number: SNCTP000000480